STEM-10. BIDIRECTIONAL INTERACTION BETWEEN TUMOR-ASSOCIATED PLATELETS AND GLIOMA STEM CELLS IN GLIOBLASTOMA MULTIFORME. (11th November 2019) - Raghavan, Alankrita; Lee-Poturalski, Christine; Willis, John; Kerstetter-Fogle, Amber; Harris, Peggy; Rich, Jeremy; Vogelbaum, Michael; Jankowsky, Eckhard; Sloan, Andrew
Abstract: Glioblastoma Multiforme (GBM) is the most common and lethal malignant primary adult brain tumor. Therapy resistance and tumor recurrence in GBM have been attributed to glioma stem cells (GSCs), which are found in hypoxic but perivascular niches. We hypothesized that the clinically documented and prognostically relevant increase in platelets in GBM promotes formation of functional hypoxic but perivascular niches that support GSCs due to formation of intravascular thromboses, a hallmark of GBM. Our preliminary in silico analysis from TCGA GBM samples indicates significant correlation of platelet and stemness signature expression (P < 0.001). High expression of platelet gene signatures also inversely correlates with overall survival in GBM patients (P < 0.02). Furthermore, we found significant co-localization of known platelet and stemness markers in primary GBM specimens, supporting our hypothesis and motivating further interrogation of GSC-platelet crosstalk. Our preliminary data suggest that GSCs exposed to either tumor or healthy platelets demonstrate increased self-renewal and stemness, as determined by a significant increase in OCT4, NANOG, and OLIG2 expression compared to unexposed GSCs. This increase in stemness and self-renewal markers was not seen in platelet-exposed differentiated glioma cell (DGC) counterparts. Conversely, platelets are stimulated by GSCs and GSC-conditioned media while DGCs elicit no stimulatory effects as measured by ATP release and aggregation assays. Our results implicate a functional role for platelet-GSC interactions in the maintenance of tumor cellular hierarchy that ultimately contributes to poor clinical outcomes in GBM. RNA-Seq of platelet-privileged GSCs is currently underway to elucidate the mechanism by which platelets impact GSC self-renewal. Successful characterization of potential crosstalk between platelets and GSCs may offer new clinical perspectives into GBM and inform development of a novel treatment paradigm to target these specific cell-to-cell interactions.